Production of blade for hydrokinetic turbine: High tech innovation fron low tech - Vitoriano, James da Rocha; Rocha, Agusto César Barreto; Lago Neto, João Caldas do (DAT Journal, 2022)
History shows us that there are many examples of humanity trying to meet its needs and solve problems through technology, using resources and knowledge to ensure its well-being. The present work intends to make a comparison between high and low technology applied in the same process of construction of wooden blades for hydrokinetic turbine, seeking to answer if it is possible to innovate using low technology? A comparative analysis will be made of the innovation with low technology, the concept of hydrokinetic turbine and the construction of its blades with high and low technology. In the analysis of examples of the manufacture of blades with high and low technology, it was found that each technology serves the consumer in a different way, the manufacture with high technology using CNC equipment, best applies to large centers, taking into account their characteristics as investment and deployment cost. For low technology, using simple woodworking tools, similar results are achieved, confirming the possibility of innovation characterized as disruptive for isolated communities, mainly promoting social development meeting the need for electricity generation.